Neurodevelopmental outcomes of extremely low birthweight infants randomised to different PCO2 targets: the PHELBI follow-up study. Issue 5 (13th January 2017) - Thome, Ulrich H; Genzel-Boroviczeny, Orsolya; Bohnhorst, Bettina; Schmid, Manuel; Fuchs, Hans; Rohde, Oliver; Avenarius, Stefan; Topf, Hans-Georg; Zimmermann, Andrea; Faas, Dirk; Timme, Katharina; Kleinlein, Barbara; et al.
Abstract : Background: Tolerating higher partial pressures of carbon dioxide (PCO2 ) in mechanically ventilated extremely low birthweight infants to reduce ventilator-induced lung injury may have long-term neurodevelopmental side effects. This study analyses the results of neurodevelopmental follow-up of infants enrolled in a randomised multicentre trial. Methods: Infants (n=359) between 400 and 1000 g birth weight and 23 0/7–28 6/7 weeks gestational age who required endotracheal intubation and mechanical ventilation within 24 hours of birth were randomly assigned to high PCO2 or to a control group with mildly elevated PCO2 targets. Neurodevelopmental follow-up examinations were available for 85% of enrolled infants using the Bayley Scales of Infant Development II, the Gross Motor Function Classification System (GMFCS) and the Child Development Inventory (CDI). Results: There were no differences in body weight, length and head circumference between the two PCO2 target groups. Median Mental Developmental Index (MDI) values were 82 (60–96, high target) and 84 (58–96, p=0.79). Psychomotor Developmental Index (PDI) values were 84 (57–100) and 84 (65–96, p=0.73), respectively. Moreover, there was no difference in the number of infants with MDI or PDI <70 or <85 and the number of infants with a combined outcome of death or MDI<70 and death or PDI<70. No differences were found between results for GMFCS and CDI. The risk factors for MDI<70 or PDI<70 were intracranial haemorrhage, bronchopulmonary dysplasia, periventricular leukomalacia, necrotising enterocolitis and hydrocortisone treatment. Conclusions: A higher PCO2 target did not influence neurodevelopmental outcomes in mechanically ventilated extremely preterm infants. Adjusting PCO2 targets to optimise short-term outcomes is a safe option. Trial registration number: ISRCTN56143743.